Modernization of Human Resource Management in Islamic Boarding Schools: An Analysis of the Outlines of Personnel and Work Systems (GBKSK) Minhajul Haq - Isrun Abdurahman; Agus Salim; Miftah Wangsadanureja; Irfan Alkhotiri; Rizaldy Alpiansyah (Labina : Journal of Islamic Education Management, 2026)
This study analyzes the Outline of Personnel and Work System (GBKSK) of the Minhajul Haq Purwakarta Islamic Boarding School as a human resource management document that integrates the values of the pesantren with modern employment principles. Using a qualitative approach with a document analysis method, this study found that GBKSK represents a form of creative resistance of Islamic boarding schools in responding to the demands of professionalization of Islamic educational institutions. This document not only regulates the technical aspects of personnel such as recruitment, rights and obligations, compensation systems, and sanction mechanisms, but also frames all employment relationships within the framework of Islamic values such as sincerity, ukhuwah Islamiyah, and manhaj Ahlussunnah wal Jamaah. Policy innovations such as Umrah and Hajj allowances, the mortgage system without usury, and the unilateral resignation sanction clause show the efforts of pesantren to create a work ecosystem that is in accordance with the characteristics of dormitory-based educational institutions. The findings of this research contribute to the development of value-based human resource management studies in Islamic educational institutions and provide an overview of how pesantren transform into modern organizations without losing their Islamic identity.